Child Care Centre services and the law in Malaysia / Aisyah Samsudin, Fatin Liyana Muhd Munif and Nur Nadiah Hamdan - Samsudin, Aisyah; Muhd Munif, Fatin Liyana; Hamdan, Nur Nadiah (2010)
This research looked into the issues of Child Care Centre (CCC) in Malaysia and the law. The method used in this research is qualitative in nature. The aim of this project is to give an overview of the services, standard of care and to highlight the challenges faced by the CCC in Malaysia. The Child Care Centre Act 1984 (Act 308) is intended to ensure quality child care for children below the age of four years at the child care centres. The caretaker of this Act is the Department of Social Welfare, Ministry of Woman, Family and Community Development. Part II of the Act 308 stipulated that every CCC must be registered under this Act. Thus, all centres that take in children for a fee are required to register with the Department of Social Welfare. The issuance of a Certificate of Registration, which has to be renewed yearly, is monitored by the Department of Social Welfare to ensure compliance with Act 308 and other regulations that come together with it. Through this research it was discovered that not many CCC are registered and the difficulty arise when they operate illegally. This project paper has thus, highlighted some of the problems raised and made some recommendations for improvement.